(untitled) (Journal of Organizational Psychology, 2022)
To address the question of why a narcissistic individual thinks and behaves the way he or she does, it is important to take an intrapersonal approach to dissect the psychological motives. The aim of this study is to further develop the concept of the narcissistic self. To specify the content and structure of the narcissistic self-concept, which we label as the dominance self-concept, we draw from the interpersonal circumplex framework of personality theories and identity motive perspective in self-system literature. Furthermore, we develop a causal-chain process model to depict the motivated process of narcissism manifestations. We contend that narcissism personality is translated into narcissistic displays through two steps of motivated links, motivated self-construal, and self-concept motivated self-regulation. In addition, we empirically test part of the process model and hypothesize a mediating role of dominance self-concept in the link between narcissism and two cognitive strategies of self-enhancement (perceived fit for leader roles, personal sense of power).